Status of Medical System During, Pre- and Post Pandemic in Relation to Preparedness - Pandey, Smriti (Digital Repository of Theses - SSBM Geneva, 2024)
A novel coronavirus was first reported in Wuhan, China in the month of December 2019. Since then, the COVID-19 pandemic has become a global emergency, with its rapid spread and high mortality rate causing severe disruptions. The primary objective of conducting research is to understand the country's situation during the pandemic and assess whether our healthcare system can handle future pandemics. To create a "pandemic-prepared" environment, the first step is to identify and classify constraints through a structured approach. This study will review various types of constraints in the healthcare industry and develop a classification method to categorize constraint factors for identification and modeling. The constraints in the healthcare industry can be broadly classified into three categories - physical, financial, and human resource constraints. Physical constraints include the availability of infrastructure, medical equipment, and supplies. Financial constraints refer to the scarcity of funds or resources, which can limit the availability of services and treatments. Human resource constraints include the availability of skilled healthcare professionals, such as doctors, nurses, and paramedics, who can provide quality care. In the later stage of this research, we will identify existing constraint modeling methods based on a comprehensive review of current industry practices and academic research. We will also develop a framework for total management that will help in the effective management of constraints in healthcare systems. To collect data, we will use probability sampling. We will use participant observation, structured interviews, and semi-structured interviews in the form of surveys and questionnaires. We will collect data from a hospital or clinic that was operational during the COVID period, the general public, the hospital staff, and doctors. The sample will be given the freedom to either participate in this research or can deny the same. Proper confidentiality will be maintained of all the participants. The information collected will be strictly used for research purposes only. The data collected will be properly analyzed. After completing the research work, we will be able to understand the shortcomings and problems that healthcare workers face during a pandemic. We will also know how much we need to push ourselves to improve healthcare in our country. The findings of this study will help policymakers and healthcare professionals to be better prepared for future pandemic-like situations.